Teachers' Perception of the Developed Physics Curriculum in e-Learning Methods during Coronavirus Pandemic - Lina Qadi (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
This study aims to detect the perception of teachers' of the developed physics curriculum; for tenth grade in the public schools affiliated with Al-Qweismeh, Amman-Jordan,;in e-learning during  the Corona virus pandemic. It also aims to study the impact of teachers' gender and qualifucations on their preciption towards e-learning. The study used a descriptive survey method. A questionnaire consisting of (17) items was applied. The study sample consisted of (158) male and female teachers. The results showed that the teachers' perceptions of the developed physics curriculum were high on all of the domains of the survey. The results also showed that there were no statistically significant differences in the perceptions of the teachers of the developed physics curriculum due to the variables gender or qualification. The study recommends paying more attention to the infrastructure that would help in e-learning. Further conducting workshops for both teachers and students in e-learning tools.  It also recommends to do similar studies in different context